Optimalisasi Digital Marketing pada UMKM pengrajin batik “Tan Collection” Binjai dalam meningkatkan penjualan - Heridayani, Heridayani; Ani, Fitri; Siregar, Prima Yanti; Dianhiny, Suci; Benny, Leo; Andrysyah, Andrysyah; Nisa, Rizki Hikmatun (Jurnal Abdi Mas Adzkia, 2025)
Digital marketing is one of the marketing methods used by MSME actors to develop their businesses. The increased use of the internet has led people to engage in modern marketing and abandon conventional marketing methods. This community service activity aims to help the problems faced by Tan Collection MSMEs. The solution offered in this activity is to implement digital marketing using Instagram. Through activities involving interviews and socialization, this aims to provide knowledge about the basic concepts of digital marketing, effective strategies, in enhancing online marketing through social media. Some digital marketing strategies that can be applied by Tan Collection MSMEs include planning a consistent posting schedule, selecting engaging content, utilizing features like Stories and Reels, or conducting live sessions. Through this community service activity, it is hoped that it can become knowledge and insight for SMEs in developing their businesses.